1973
DOI: 10.2307/1366565
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of Burrowing Owl Ecology and Behavior

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and CooperOrnithological Society are collaborating with JSTOR to digitize, preserve and extend access to The Condor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 10 publications
(28 reference statements)
7
80
0
9
Order By: Relevance
“…In contrast, ground-foraging and the use of perches are strategies employed by Burrowing Owls, indicating that this owl is predominantly a sit-and-wait predator (Thomsen 1971, Marti 1974, Jaksic and Carothers 1985. Further, Burrowing Owls are diurnal/crepuscular, (Thomsen 1971, Martin 1973, whereas Barn Owls are primarily nocturnal (Bunn et al 1982). Although both owls use vision to hunt, Barn Owls are capable of seeing at lower light intensity than Burrowing Owls (Marti 1974).…”
Section: Selecció N De Pequeñ Os Mamíferos Como Presas Por Parte De Dmentioning
confidence: 99%
“…In contrast, ground-foraging and the use of perches are strategies employed by Burrowing Owls, indicating that this owl is predominantly a sit-and-wait predator (Thomsen 1971, Marti 1974, Jaksic and Carothers 1985. Further, Burrowing Owls are diurnal/crepuscular, (Thomsen 1971, Martin 1973, whereas Barn Owls are primarily nocturnal (Bunn et al 1982). Although both owls use vision to hunt, Barn Owls are capable of seeing at lower light intensity than Burrowing Owls (Marti 1974).…”
Section: Selecció N De Pequeñ Os Mamíferos Como Presas Por Parte De Dmentioning
confidence: 99%
“…In a New Mexico study the observed population densities were evidently considerably lower (15 pairs located along 3.7 linear kilometers of hab-itat) and territory sizes correspondingly higher, in spite of available and apparently suitable burrow sites in the area; there the average distance between occupied nests was 166 meters (Martin, 1973a). Grant (1965) estimated that 5-9 pairs nested in an area of 32 hectares in North Dakota, suggesting a nesting density of 3.5-6 hectares per pair, and Wedgewood (1976) also found a colony of 6-8 active burrows in a Saskatchewan pasture of about 100 hectares, or about 13-16 hectares per pair.…”
Section: Habitats and Ecologymentioning
confidence: 92%
“…Low vegetation around the nesting site may also increase hunting efficiency. Burrows Martin, 1973a), (C-D) variations in exposure of white throat and white facial feathers (after Thomsen, 1971), (E) precopulatory posture (female on right, after Coulombe, 1971), and (F) nest-defense posture (after Bent, 1938). located in relatively sandy sites may also be favored there, perhaps because they are more \ \ easily modified by enlarging passageways and \.,1 may also drain more rapidly following rainfall. However, Rich (1986) found in Oregon that the birds preferred to nest in small rock outcrops, perhaps for reasons of increased safety against badgers (Taxadea taxus) and canid predators.…”
Section: Habitats and Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Su ecología trófica ha sido estudiada tanto en el hemisferio norte (e.g., Thomsen, 1971;Martin, 1971Martin, , 1973Maser et al, 1970Maser et al, , 1971Hennemann & Willard, 1980;Tyler, 1983;MacCracken et al, 1985;Thompson & Anderson, 1988;Green et al, 1993;Plumpton & Lutz, 1993a;John & Romanow, 1993, 1998Haug et al, 1993;Morgan et al, 1994;Sissons et al, 2001;Valdéz-Gómez & Rocha, 2005;Littles et al, 2007;Wiley, 2008;Gervais et al, 2000;York et al, 2002;Klute et al, 2003;Moulton et al, 2005;Valdéz-Gómez & Enríquez-Rocha, 2005;Poulin et al, 2011), como en el hemisferio sur (e.g., Yañez & Jaksic, 1979;Pulido & Aguilar, 1979;Jaksic & Schlatter et al, 1980;Marti, 1981;Núñez & Yánez, 1982;Bellocq, 1987;Meserve et al, 1987;Massoia et al, 1988;Martins & Eglar, 1990;Silva-Porto & Cerqueira, 1990;Soares et al, 1992;Bellocq & Kravetz, 1994;Torres-Contreras et al, 1994;Vieira & Teixeira, 1996;De Santis et al, 1997;…”
Section: áRea De Estudiounclassified